Penguatan Keunggulan Bersaing BUMDes Melalui Local Wisdom Dalam Pemulihan Ekonomi di Provinsi Bali Pasca Pandemi Covid -19 - Ni Nyoman Adityarini Abiyoga Vena Swara; Ni Luh Adisti Abiyoga Wulandari (UNHI Press, 2023)
BUMDes plays a role as a driving force for the economy of the village community so that the independence and welfare of the village community is realized. Seeing the important role of BUMDes in economic development and empowering rural communities, BUMDes requires the right quality business strategy to support BUMDes' competitive advantage and performance. The competitive advantage of BUMDes is developed through village business management based on local resources by prioritizing local wisdom values ??owned by the community. The research was conducted at BUMDes in nine regencies/cities in Bali Province. This research is an Explanatory Research using a survey method in the form of distributing questionnaires. Data analysis techniques using Path Analysis and Sobel Test. The results of the study show that the quality of business strategy has a positive and significant effect on competitive advantage and BUMDes performance and competitive advantage plays a role in mediating the effect of the quality of business strategy on BUMDes performance. Based on the research results, BUMDes should be able to optimize the potential utilization of economic resources, natural resources, and human resources which can be managed into strategic assets so that BUMDes can become a cog for the village economy after the Covid-19 Pandemic.